Spectral energy distributions and age estimates of 40 massive young stellar objects - Tanti, K.K.; Roy, J.; Duorah, K. (Advances in Astronomy and Space Physics, 2012)
In this paper, we present the spectral energy distributions (SEDs) of 40 massive young stellar objects (YSOs), detected from the NIR imaging survey carried out by Varricatt et al. 2010 and estimated their ages and masses. The SEDs of YSOs in 40 massive star forming regions have been reconstructed using 2MASS, MSX, IRAS, IRAC & MIPS, SCUBA, WISE, SPIRE and IRAM data, partly available from previous works, using the on-line SED Fitting tool (SED Fitter) developed by Robitaille et al. 2006, 2007. Apart from IRAS catalogue fluxes, the fluxes in the Mid-IR and sub-mm/mm were derived directly from the images. With the help of the analysis of SEDs, we have extracted important physical and structural parameters for each of the massive young stellar objects, along with the associated circumstellar disk and envelope. The cumulative distribution of the stellar ages and masses of the massive YSOs lead to a scenario for the formation history of massive stars in their respective star forming regions.